The Influence Of Work Ethic On Employee Performance (Study At The Library And Archives Office Of Garut District) - Santanu, Tita Rachtawati (UNIVERSITAS PAKUAN, 2020)
The purpose of this research is to determine the influence of work ethic on employee performance at the Garut Regency Library and Archives Service. The type of research used in this research is quantitative with a descriptive method approach and an associative method. The population in this study was 43 people, with a total of employees of the Garut Regency Library and Archives Service. Data collection techniques and tools are interviews, questionnaires and literature studies. The data analysis technique used is in the form of statistical formulas in the form of validity tests, reliability tests, correlation coefficient tests, determination coefficient tests, and hypothesis coefficient tests. Based on the results of the correlation test, a result of 0.610 was obtained, which is in the